2012
DOI: 10.1007/s10692-012-9401-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic analysis of monomers in the production of threads from aromatic polyamides

Abstract: OAO Kamenskvolokno is a domestic industrial manufacturer of aramid threads. Specialists of the firm pay special attention to analytical production control at all stages, from starting material analysis, at intermediate synthetic steps of the aromatic copolyamide, to release of the final product, in order to improve the production process. Special attention is paid to the purity of the diamines and aromatic acid anhydrides. The monomers for manufacture of aramid threads are aromatic diamines [1] 5(6)-amino-2-(p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that tea polyphenols are able to scavenge nitrite and JFDS-2019-0460 Submitted 3/30/2019, Accepted 6/24/2019 inhibit the N-nitrosation of secondary amines effectively both in vitro and in vivo (Nakamura & Kawabata, 2010;Ohsawa et al, 2003;Tanaka, Hayatsu, Negishi, & Hayatsu, 1998). Recently, catechins, the active bio-compounds rich in polyphenols, showed significant capacities to reduce residual nitrite content in cured meats, thus blocking N-nitrosamine formation (Moawad, Abozeid, & Nadir, 2012;Wang et al, 2015). The observed blocking effects may be ascribed to the mechanisms that polyphenols could scavenge the nitrosating agent by reacting with nitrite to form phenol derivatives, ultimately inhibiting the N-nitrosation of amines (Lu, Dong, Li, & He, 2016;Panzella, Manini, Napolitano, & D'Ischia, 2005;Vermeer, Moonen, Dallinga, Kleinjans, & Maanen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that tea polyphenols are able to scavenge nitrite and JFDS-2019-0460 Submitted 3/30/2019, Accepted 6/24/2019 inhibit the N-nitrosation of secondary amines effectively both in vitro and in vivo (Nakamura & Kawabata, 2010;Ohsawa et al, 2003;Tanaka, Hayatsu, Negishi, & Hayatsu, 1998). Recently, catechins, the active bio-compounds rich in polyphenols, showed significant capacities to reduce residual nitrite content in cured meats, thus blocking N-nitrosamine formation (Moawad, Abozeid, & Nadir, 2012;Wang et al, 2015). The observed blocking effects may be ascribed to the mechanisms that polyphenols could scavenge the nitrosating agent by reacting with nitrite to form phenol derivatives, ultimately inhibiting the N-nitrosation of amines (Lu, Dong, Li, & He, 2016;Panzella, Manini, Napolitano, & D'Ischia, 2005;Vermeer, Moonen, Dallinga, Kleinjans, & Maanen, 1999).…”
Section: Introductionmentioning
confidence: 99%